1988
DOI: 10.1002/hep.1840080516
|View full text |Cite
|
Sign up to set email alerts
|

Galactose elimination capacity and liver volume in aging man

Abstract: The galactose elimination capacity, a measure of the functional liver cell mass, and liver volume were measured in 50 normal subjects of five different age groups (less than 50, 51 to 60, 61 to 70, 71 to 80 and greater than 81 years). The volume of the liver was evaluated by ultrasonography. All subjects had normal routine liver function tests and no history of liver disease. Galactose elimination progressively decreased from 3.05 +/- 0.58 (S.D.) mmoles per min in younger subjects to 1.83 +/- 0.24 mmoles per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 20 publications
8
66
1
Order By: Relevance
“…This study confirms the known negative correlation between age and TLV. 23,24 However, this effect of age on the correlation between BSA and TLV is negligible. This finding facilitates comparison of the current formula with other formulas and simplifies the calculation of TLV in a clinical setting.…”
Section: Discussionmentioning
confidence: 98%
“…This study confirms the known negative correlation between age and TLV. 23,24 However, this effect of age on the correlation between BSA and TLV is negligible. This finding facilitates comparison of the current formula with other formulas and simplifies the calculation of TLV in a clinical setting.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported that liver mass declines >40% in humans during the first two to three decades of life, but that it remains virtually stable thereafter (7). Two more recent studies, using more sophisticated and sensitive measurements, concluded that liver volume declines between maturity and senescence in humans (8,9). The implications of reduced liver volume and hepatic blood flow in the elderly are unclear, but may have a critical impact on such parameters as the pharmacokinetic profiles of drugs that undergo mandatory hepatic oxidation.…”
Section: Liver Morphologymentioning
confidence: 99%
“…A recent correlated in vivo and in vitro study in humans suggested that a 30% decline in hepatic drug metabolism after 70 years of age reflected similar reductions in the liver cytochromes P-450 content and antipyrine clearance rate (65). However, two 1988 studies have shown that liver volume and hepatic blood flow in healthy, ambulatory elders declines appreciably in comparison to young subjects (8,9). The losses of liver mass and hepatic blood flow, rather than intrinsic alterations to constituents of the microsomal monooxygenase system, contribute to reduced drug clearance in the elderly subjects.…”
Section: Hepatic Functionmentioning
confidence: 99%
“…Four patients had mild asciuretics and lactulose) were continued unchanged throughout tes at ultrasonography, which was not clinically evident, and the study period. Patients were regularly followed as outpaall were being treated with diuretics (spironolactone [100-tients (every month), and compliance to zinc treatment was 200 mg/d] and/or furosemide [25 mg/d]) and lactulose (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) checked by counting the number of tablets not used in the g/d). Clinical evidence of chronic hepatic encephalopathy was, previous 30 days.…”
mentioning
confidence: 99%